Respuesta :

Answer:

x=+6

Step-by-step explanation:

First, let's divide both sides of the equation by  

3

:

3

x

2

3

=

108

3

x

2

=

36

Then, let's subtract  

36

from both sides:

x

2

36

=

36

36

x

2

36

=

0

The left-hand side of the equation is now in the form of a difference of squares.

We can factorise it in the following way:

(

x

+

6

)

(

x

6

)

=

0

Using the null factor law:

x

=

±

6

Therefore, the solutions to the equation are  

x

=

6

and  

x

=

6

.

ACCESS MORE